A historical review of the Chinese documentary programs - Li, Mengyu; Yasin, Megat Al Imran; Hashim, Norliana; Ang, Lay Hoon (Innovare Academics Sciences, 2020)
This study is to review the source, development, and evolution of Chinese documentary programs through the historical dimension; it can better draw production experience and improve the creative ability for the producers. From the founding of China to the present, the changes of Chinese documentary programs can be divided into six different historical stages. Moreover, the content of Chinese documentary programs has origins in China's political background, especially Chinese unique social nature and cultural traditions. As a result, they continue to evolve as China changes. In particular, with the rapid development of China's economy, on the one hand, Chinese television stations continue to invest in the creation of documentary programs to consolidate their audience. On the other hand, online platforms have opened up new channels for viewing documentaries. Chinese documentary programs have become a window for audiences at home and abroad to learn about Chinese history, culture, and tradition. The use of Chinese documentary programs to tell China’s story will show the real, three-dimensional, and comprehensive picture of China to the whole world.